The Effect Fish Bone Shape Strategy In Achievement Fourth Primary Female Pupils And Mathematical Thinking Grade - Shaymaa Kareem Hassoon ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The recent research aims to identify the effect fish bone shape Strategy on achievement and mathematical thinking and achievement of fourth primary grade female pupils, The sample of the research was limited by fourth primary grade female pupils of Al – Mutanabi girls, school – directed general of Masan, This school consists of three divisios sections, So section (A) were chosen to be the control group which were taught by the traditional method while section (C) were chosen to be the experimental group which were taught by fish bone shape Strategy, The sample contains (40) female pupil, so the experimental group consists of (20) female pupil and the control group also consists of (20) female pupil, The pretest of achievement test consisting of (20) items, And mathematical thinking domain(induction, expression by symbols, problem solution) consisting of (12) items, Which is divided to (8) objective items and (4) subjective items, The face validity and the content validity were verified, The (Alfa – cronbaghe) equation was used to calculate the reliability to thinking test and Kiodr equation 20 to achierement test, the researcher has user (t-test) to the two groups to treat The conclusion: 1 – The using of fish bone shape Strategy has an effect on the achievement of fourth primary grade female pupils 2 – The using of fish bone shape Strategy has an effect on mathematical thinking of fourth primary grade female pupils